Community-associated methicillin-resistant Staphylococcus aureus: molecular and epidemiological aspects - Luján Roca, Daniel Angel (2013)
Community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is broadly disseminated in the world, is epidemic in some countries and possesses two characteristic molecular markers: SCCmec IV and Panton-Valentine leukocidin, both scarcely found in healthcare-associated MRSA.